Antimicrobial activity of calcium hydroxide, calcium oxide, and mineral trioxide aggregate paste against α-Hemolytic Streptococcus - Darmadi, Eveline Yulia; Soesilo, Diana (Conservative Dentistry Journal, 2024)
Background: The bacteria mostly found in the root canals are aerobic and facultative anaerobic bacteria, such as α-Hemolytic Streptococcus. Calcium hydroxide has alkaline characteristics with pH of 12.5, and antimicrobial properties. Calcium oxide is hydrophilic and has a smaller molecular weight than calcium hydroxide. Mineral trioxide aggregate (MTA) has alkaline properties, good biocompatibility, stimulates healing and inhibits bacterial growth. Purpose: The purpose of this study was to examine the differences of antimicrobial activity between calcium hydroxide, calcium oxide, and mineral trioxide aggregate (MTA), also to find which of these materials has the highest antimicrobial activity. Methods: The design of this study was a post-test only control group design. The study subjects were divided into 4 groups. K (-) was control group without any treatment, P1 was treated with calcium hydroxide, P2 was treated with calcium oxide, and P3 was treated with MTA. Each group consisted of 7 samples. The α-Hemolytic Streptococcus were spread on Mueller Hinton agar. Antimicrobial test was using diffusion method and diameter of inhibition zones were measured with caliper. Results: Average inhibitory zone of each sample was P1 (30.9643 mm ± 0,7431), P2 (35,2357 mm ± 0,7099), P3 (28,6 mm ± 1,5532). Tukey HSD test showed significances results between samples P1 and P2 (p=0,001), P1 and P3 (p=0,002), P2 and P3 (p=0,001). Conclusion: The highest antimicrobial activity against α-Hemolytic Streptococcus was calcium oxide followed by calcium hydroxide and MTA.